Human engineered cardiac tissue model of hypertrophic cardiomyopathy recapitulates key hallmarks of the disease and the effect of chronic mavacamten treatment - Wang, Kai; Schriver, Brian J.; Aschar-Sobbi, Roozbeh; Yi, Alex Y.; Feric, Nicole T.; Graziano, Michael P. (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: The development of patient-specific induced pluripotent stem cell-derived cardiomyocytes (iPSC-CMs) offers an opportunity to study genotype-phenotype correlation of hypertrophic cardiomyopathy (HCM), one of the most common inherited cardiac diseases. However, immaturity of the iPSC-CMs and the lack of a multicellular composition pose concerns over its faithfulness in disease modeling and its utility in developing mechanism-specific treatment. Methods: The Biowire platform was used to generate 3D engineered cardiac tissues (ECTs) using HCM patient-derived iPSC-CMs carrying a β-myosin mutation (MYH7-R403Q) and its isogenic control (WT), withal ECTs contained healthy human cardiac fibroblasts. ECTs were subjected to electro-mechanical maturation for 6 weeks before being used in HCM phenotype studies. Results: Both WT and R403Q ECTs exhibited mature cardiac phenotypes, including a lack of automaticity and a ventricular-like action potential (AP) with a resting membrane potential < −75 mV. Compared to WT, R403Q ECTs demonstrated many HCM-associated pathological changes including increased tissue size and cell volume, shortened sarcomere length and disorganized sarcomere structure. In functional assays, R403Q ECTs showed increased twitch amplitude, slower contractile kinetics, a less pronounced force-frequency relationship, a smaller post-rest potentiation, prolonged AP durations, and slower Ca2+ transient decay time. Finally, we observed downregulation of calcium handling genes and upregulation of NPPB in R403Q vs. WT ECTs. In an HCM phenotype prevention experiment, ECTs were treated for 5-weeks with 250 nM mavacamten or a vehicle control. We found that chronic mavacamten treatment of R403Q ECTs: (i) shortened relaxation time, (ii) reduced APD90 prolongation, (iii) upregulated ADRB2, ATP2A2, RYR2, and CACNA1C, (iv) decreased B-type natriuretic peptide (BNP) mRNA and protein expression levels, and (v) increased sarcomere length and reduced sarcomere disarray. Discussion: Taken together, we demonstrated R403Q ECTs generated in the Biowire platform recapitulated many cardiac hypertrophy phenotypes and that chronic mavacamten treatment prevented much of the pathology. This demonstrates that the Biowire ECTs are well-suited to phenotypic-based drug discovery in a human-relevant disease model.